International Monetary Fund Annual Report 1981. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1981)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1981. The report highlights that the world economic situation during 1980 and the first half of 1981 was difficult and disappointing in important respects. Nevertheless, signs of progress in dealing with some of the severe economic problems of recent years have begun to emerge. Both the encouraging aspects of the situation and the difficulties confronting national authorities, as well as the policies being utilized to meet those difficulties, are outlined in this report.